Reevaluation of FMR1 Hypermethylation Timing in Fragile X Syndrome - Mor-Shaked, Hagar; Eiges, Rachel (Frontiers in Molecular Neuroscience, 2018)
Fragile X syndrome (FXS) is the most common heritable form of cognitive impairment. It results from a FMRP protein deficiency caused by a CGG repeat expansion in the 5'-UTR of the X-linked FMR1 gene. Whereas in most individuals the number of CGGs is steady and ranges between 5 and 44 units, in patients it becomes extensively unstable and expands to a length exceeding 200 repeats (full mutation). Interestingly, this disease is exclusively transmitted by mothers who carry a premutation allele (55-200 CGG repeats). When the CGGs reach the full mutation range, they trigger the spread of abnormal DNA methylation, which coincides with a switch from active to repressive histone modifications. This results in epigenetic gene silencing of FMR1 presumably by a multi-stage, developmentally regulated process. The timing of FMR1 hypermethylation and transcription silencing is still hotly debated. There is evidence that hypermethylation varies considerably between and within the tissues of patients as well as during fetal development, thus supporting the view that FMR1 silencing is a post-zygotic event that is developmentally structured. On the other hand, it may be established in the female germ line and transmitted to the fetus as an integral part of the mutation. This short review summarizes the data collected to date concerning the timing of FMR1 epigenetic gene silencing and reassess the evidence in favor of the theory that gene inactivation takes place by a developmentally regulated process around the 10th week of gestation.